2014
DOI: 10.1111/abac.12035
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Country, Industry, and Topic Factors on IFRS Policy Choice

Abstract: This paper proposes a framework for understanding management's decision-making on observable accounting policy choices. The framework is used to hypothesize how country, industry, and topic factors influence policy choice under International Financial Reporting Standards (IFRS). The hypotheses are tested on the choices made by the largest firms from 10 jurisdictions on a comprehensive set of IFRS policy topics, which are hand-collected from the financial statements. The results are consistent with the framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 35 publications
1
42
1
14
Order By: Relevance
“…Such differences occur because despite the international standards, the preparers are still local and therefore influenced by local accounting practices. Such differences can be empirically found in the choices made by preparers regarding IFRS policy options (Kvaal & Nobes, 2010;Nobes, 2011;Nobes & Stadler, 2013;Stadler & Nobes, 2014). These differences, which are based on classes drawn up since the 1960s, lead us, once again, to find two separate groups: the Anglo and the Continental European.…”
Section: Discussionmentioning
confidence: 97%
“…Such differences occur because despite the international standards, the preparers are still local and therefore influenced by local accounting practices. Such differences can be empirically found in the choices made by preparers regarding IFRS policy options (Kvaal & Nobes, 2010;Nobes, 2011;Nobes & Stadler, 2013;Stadler & Nobes, 2014). These differences, which are based on classes drawn up since the 1960s, lead us, once again, to find two separate groups: the Anglo and the Continental European.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the common use of international accounting standards, his findings show that remain the two traditional groups: 1) Anglo-Saxon (Australia, UK) and 2) Continental European (Sweden, Germany, France, Italy, Nederland e Spain). Later, also many other empirical analyses found that there are still a lot of relevant differences in applying IAS/IFRS (Nobes & Stadler, 2013) due both to various options and ambiguous interpretations (Kvaal & Nobes, 2010, 2012Nobes, 2006Nobes, , 2008Nobes, , 2011Nobes, , 2013Stadler & Nobes, 2014) and to the presence of label serious firms adopters (Daske et al, 2013).…”
Section: Classification Of Countries By Their Accounting Practices: Amentioning
confidence: 99%
“…Contrary to what one might suppose, many empirical analyses found that there are still a lot of relevant differences in applying IAS/IFRS. It is substantially due both to their principles-based approach that could allow various options and ambiguous interpretations (Ball, 2006;Kvaal & Nobes, 2010, 2012Nobes, 2006Nobes, , 2008Nobes, , 2011Nobes, , 2013Stadler & Nobes, 2014;Forst & Salerno, 2016) and to the presence of firms that adopt them more in name (-label firms‖), than as a part of a strategy to increase their commitment to transparency (-serious firms‖) (Daske et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Na identificação do principal determinante das escolhas entre práticas permitidas, o fator país tem sido o mais importante (Stadler & Nobes, 2014). Jaafar e Mcleay (2007) apresentam um contraponto e reinterpretam o conceito de harmonização, ao afirmarem que se presume que a contabilidade será completamente harmonizada quando todas as empresas, que operam em circunstâncias similares, adotarem idêntico tratamento contábil para transações similares sem considerar seu domicílio.…”
Section: Introductionunclassified